Hematology and blood chemistry values in free-living Imperial Cormorants (Phalacrocorax atriceps) - Gallo, Luciana; Quintana, Flavio Roberto; Svagelj, Walter Sergio; Uhart, Marcela (Avian Diseases)
As part of an on-going long-term study on the reproductive ecology and health status of imperial cormorants (Phalacrocorax atriceps), blood samples were collected to establish baseline values for hematological parameters (hematocrit, red and white blood cell counts, leukocyte profile, heterophil/lymphocyte ratio, total solids) and serum chemistries (glucose, uric acid, urea, total protein, triglycerides, cholesterol, albumin/globulin ratio, alkaline phosphatase, lactate dehydrogenase, creatine phosphokinase, aspartate aminotransferase, alanine aminotransferase, calcium, phosphorus). One hundred and eighty-four male adults from the Punta León breeding colony in Patagonia Argentina, were captured during the chick-rearing period of four breeding seasons, 2004 (n= 48), 2005 (n= 29), 2010 (n= 43) and 2011 (n= 64). All birds appeared to be in good body condition and no abnormalities were noted during physical examination. In general, values for the parameters reported in this study were similar to those previously described for other cormorant species. Significant inter-annual differences were observed in most health parameters analyzed. This study defines baseline health parameters for imperial cormorants, and coupled with previous reports on pathogen exposure, contributes to our knowledge the overall health status of the species. Como parte de un estudio a largo plazo sobre la ecología reproductiva y el estado sanitario del cormorán imperial (Phalacrocorax atriceps), se recolectaron muestras de sangre para establecer los valores de referencia de parámetros hematológicos (hematocrito, conteo total de eritrocitos y leucocitos, perfil leucocitario, proporción heterófilos∶linfocitos, sólidos totales) y bioquímicas plasmáticas (glucosa, ácido úrico, urea, proteínas totales, triglicéridos, colesterol, proporción albúmina∶globulina, fosfatasa alcalina, lactato deshidrogenasa, creatina fosfoquinasa, aspartato aminotransferasa, alanina aminotransferasa, calcio, fósforo). Se capturaron 184 machos adultos en la colonia ...